IMPOR BERAS DAN IMPLIKASI KEBIJAKAN PRODUKSI DAN KONSUMSI BERAS DI INDONESIA - Helmi Noviar (JURNAL EKOMBIS, 2018)
The purpose of this paper is to assess the implications of rice imports on the welfareof farmers and several factors that cause rice imports in Indonesia. The method usedis a collection of data generated from various publications / publishing from the Indonesian Central Bureau of Statistics, and formerly comparing the various results that resulted in journal publications. The results of analysis in this paper, based onrecent data, find the production gap between production and consumption which driven by the rate of consumption growth is not corresponding by the rate of growthof production. Thus, to carry out this issue, the government require import rice policyin 2014.This implies a decline in the purchasing power of farmers (NTP) and farmerproduction (NTUP) which in the next year increase rice production (2015) but it cannot significantly boost both competitiveness indicators. Therefore, in the short run, the imposition of rice commodities must be carefully calculated using the right principles and in the long term the increase of national rice production must be doneby improving facilities and infrastructure in the agricultural sector, and access to capital so as to create professional cooperation as rice producer in indonesia.Keywords: rice importation, production-consumption gap, NTP/NTUP.